2003
DOI: 10.1017/s0269964803174062
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for the Distribution of Two-Dimensional Binary Scan Statistics

Abstract: In the present article we develop some efficient bounds for the distribution function of a two dimensional scan statistic defined on a (double) sequence of iid binary trials. The methodology employed here takes advantage of the connection between the scan statistic problem and a equivalent reliability structure and exploits appropriate techniques of reliability theory to establish tractable bounds for the distribution of the statistic of interest. An asymptotic result is established and a numerical study is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We compare numerically our results with results obtained using the product approximation, the Poisson approximation and Bonferroni inequality techniques as presented in Glaz et al (2001). For binary Y i,j 's we compare our values to bounds obtained in Boutsikas and Koutras (2003).…”
Section: Two Dimensional Discrete Scan Statisticmentioning
confidence: 93%
“…We compare numerically our results with results obtained using the product approximation, the Poisson approximation and Bonferroni inequality techniques as presented in Glaz et al (2001). For binary Y i,j 's we compare our values to bounds obtained in Boutsikas and Koutras (2003).…”
Section: Two Dimensional Discrete Scan Statisticmentioning
confidence: 93%
“…Many studies on 2-dimensional discrete scan statistics can be found in Chapter 16 of Glaz, Naus, and Wallenstein [11]. Recently, Boutsikas and Koutras [7] had proposed some bounds on 2-dimensional discrete scan statistics and reported asymptotic results on them (an anonymous referee pointed out this for us).…”
Section: The 2-dimensional Rectangular K-within-consecutive-(r S)-oumentioning
confidence: 99%
“…Since there are no exact formulas for P(S ≤ n), various methods of approximation and bounds have been proposed by several authors. An overview of these methods as well as a complete bibliography on the subject can be found in Chen and Glaz [1996], Glaz, Naus and Wallenstein [2001, Chapter 16], Boutsikas and Koutras [2003], Haiman and Preda [2006] and the references therein.…”
Section: Introductionmentioning
confidence: 99%